Reaction of Chenopodium quinoa to different species of Meloidogyne - Mendoza-Lima, Maria Yaquelin (2020)
Currently, there are no studies on the cultivation of quinoa (Chenopodium quinoa) in Peru related to the reaction ofMeloidogynespp. Thisstudy aimed to evaluate the reaction of five quinoa cultivars (‘Salcedo INIA’, ‘Choclito’, ‘Huariponcho’, ‘Negra Collana’, and ‘Kcancolla’)toMeloidogyne arenaria, Meloidogyne incognita,andMeloidogyne hapla. The experiment was carried out using a completely randomizeddesign, with five quinoa cultivars and three species ofMeloidogynespp. with six repetitions. Quinoa plants were kept in a mesh house andplaced in polyethylene bags with 3,000 dm³ of sterile soil inoculated with 5,000 eggs + juveniles (J2). After 90 days of inoculation, thenumber of nematodes per gram of root, number of galls, and the reproduction factor (final population/initial population) were determined.All quinoa cultivars were susceptible toM. incognitaand resistant toM. arenariaandM. hapla,except for ‘Negra Collana’, which wassusceptible toM. arenaria, and ‘Salcedo INIA’ and ‘Huariponcho’, susceptible toM. hapla.